Determinants of local government financial performance: The mediating role of e-government - Nasution, Ichlasul Amin; Yudianto, Ivan; Mulyani, Sri (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study examines the impact of capital expenditures, follow-up on audit recommendations, and local government financial performance, with e-government as moderating variable. Methodology/approach: The research used quantitative data from 2019–2022, this study employs purposive sampling and panel data regression with moderated regression analysis. Results/findings: The research results show that capital expenditure has a negative but insignificant effect. Follow-up on audit recommendations has a positive but insignificant effect. Horizon problems significantly and negatively impact financial performance. E-government as a moderating variable is only effective in reducing the negative impact of the horizon problem, but it cannot strengthen the positive influence of capital expenditure or audit follow-up on financial performance. Conclusion: Capital expenditure shows ineffectiveness despite meeting the spending threshold. The follow-up on audit recommendations shows that only 5 out of 34 provinces met the BPK target, and 39% of the recommendations align with the findings. horizon issue with 35% of provinces experiencing a decline in revenue during 2019–2024. E-government in capital expenditure only focuses on administrative function. SPBE index cannot enhance financial performance. But, reduces negative effects horizon problem through data-based prioritization and real-time budget allocation with e-budgeting system. Limitations: Financial performance measurement focus on regional original revenue, and e-government implementation requires more detailed evaluation. Contribution: The findings offer policymakers and public insights to prioritize strategies enhancing local government financial performance.